Grapevine cv. 'Riesling' water use in the northeastern United States - Intrigliolo, Diego S.; Lakso, A. N.; Piccioni, R. M. (2017)
Vine water use was measured in a Vitis vinifera cv. Riesling vineyard located in New York. Vines were fully irrigated and were trained via vertical shoot positioning giving a narrow curtain intercepting about 30% of the incident light during the sunlight hours. Vine water use was estimated on six vines by sap flow gauges directly calibrated with whole canopy transpiration measurements. The regression analysis between estimates of transpiration showed that there were large differences between vines in the calibration values obtained. Sap flow monitoring started late in June, about 2 weeks after bloom, when the canopy already filled the trellis system, and continued until October. Results showed that vine water use during most of the summer days was between 1.0 and 2.0 mm day(-1), with peak values around 2.5 mm. The basal (e.g. vine transpiration/reference evapotranspiration) crop coefficient (K (cb)) varied somewhat between days, but it was quite stable during the whole season. Averaged over the entire experimental period, the K (cb) was 0.49. Some of the day-to-day variation in the K (cb) was negatively related with daily average air vapour pressure deficit. This suggests that reference evapotranspiration models on grass may not be fully accurate for vines under these experimental conditions.